2001
DOI: 10.1046/j.1440-1681.2001.03586.x
|View full text |Cite
|
Sign up to set email alerts
|

Mineralocorticoids and Cardiac Fibrosis: The Decade in Review

Abstract: 1. Over the past decade, aldosterone has been shown to have direct extra-epithelial actions and substantial (patho)physiological roles in the cardiovascular system in the context of inappropriate salt status. In experimental studies on uninephrectomized rats given 0.9% NaCl solution to drink, these include blood pressure elevation via activation of circumventricular mineralocorticoid receptors in the central nervous system and production of pressure-independent cardiac hypertrophy and fibrosis by a direct effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
54
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 29 publications
2
54
0
3
Order By: Relevance
“…1 This study, along with many translational reports, strongly developed the concept that aldosterone may play an important, deleterious effect in human congestive heart failure. [2][3][4][5] In addition, we have previously observed that aldosterone has rapid, inotropic effects in the isolated perfused rat heart; 6 however, rapid, inotropic effects were observed as early as the 1960s. 7,8 This rapid, inotropic effect of aldosterone almost certainly occurs through nongenomic mechanism(s).…”
mentioning
confidence: 96%
“…1 This study, along with many translational reports, strongly developed the concept that aldosterone may play an important, deleterious effect in human congestive heart failure. [2][3][4][5] In addition, we have previously observed that aldosterone has rapid, inotropic effects in the isolated perfused rat heart; 6 however, rapid, inotropic effects were observed as early as the 1960s. 7,8 This rapid, inotropic effect of aldosterone almost certainly occurs through nongenomic mechanism(s).…”
mentioning
confidence: 96%
“…Several studies have shown vascular and target-organ protective effects of aldosterone receptor antagonism. [1][2][3][4] In aldosteroneinfused rats, spironolactone or the more specific antagonist eplerenone prevents inflammation and fibrosis in the heart, blood vessels, and kidney; improves endothelial function; and reduces activation of NAD(P)H oxidase. [5][6][7][8][9] In animal models of hypertension, such as stroke-prone spontaneously hypertensive rats, aldosterone receptor antagonism also reduced vascular remodeling and renal damage, particularly in the presence of high salt.…”
mentioning
confidence: 99%
“…The mechanisms of this action in cardiac remodeling are not fully understood. The antiarrhythmogenic benefits of MR antagonists might be linked to their role in ameliorating reactive fibrosis 8,9 and/or, alternatively, to their electrophysiological effects. Recently, we showed that aldosterone treatment of isolated myocytes mimics the electrophysiological changes that occur during cardiac remodeling.…”
mentioning
confidence: 99%